When Digital HRM Meets Human Readiness: Explaining of Innovative Work Performance Through AI Readiness and Psychological Safety - Vellen Wibowo (Riviera Publishing, 2026)
The pace of digital transformation in higher education also promotes universities to incorporate digital Human Resource Management (HRM) systems, such as AI-aided recruitment, digital performance management, and online learning platforms. But technological adoption is not enough to induce employees to create more innovation and better performance. This research investigated AI readiness as a strategic human capital capability that provides the organizational framework through which digital infrastructure and psychological climate are linked to innovative work outcomes among university lecturers. Based on the Resource-Based View (RBV) and Dynamic Capability Theory, the research assesses the associations between Digital HRM Capability, Digital Psychological Safety Climate, AI Readiness, and Innovative Work Performance. Data was obtained through a cross-sectional survey of Indonesian lecturers, using a quantitative explanatory design, and analyzed through Structural Equation Modeling (SEM). The findings suggest that the positive relationships between the two factors of Digital HRM Capability and Digital Psychological Safety Climate in predicting AI Readiness will greatly boost Innovative Work Performance. In addition, AI Readiness mediates antecedent effects on Innovative Work Performance. These results suggest that successful university digital transformation is not merely about the deployment of technological platforms, but also the preparedness of staff to utilize AI and an environment that is psychologically supportive of digital experimentation.